The Role of Knowledge Sharing in Mediation The Influence of Self-Efficiency on Lecturer Performance - Rasyid, Rohsita Amalyah; Adinugroho, Iwan; Suwanti, Suwanti; Amalia, Amalia (Universitas Negeri Makassar, 2021)
The purpose of this study was to analyze the role of knowledge sharing in mediating the effect of self-efficacy on lecturer performance by examining the effect of self-efficacy on lecturer performance and the role of knowledge sharing as an intermediary variable. The research data was obtained from questionnaire answers which included 38 respondents from permanent lecturers at the Muhammadiyah Mamuju College of Economics who had functional positions selected based on purposive sampling. The results showed that self-efficacy has a significant effect on lecturer performance, and self-efficacy also has a significant effect on the mediating variable of knowledge sharing. Meanwhile, knowledge sharing did not mediate the self-efficacy variable on lecturer performance. Several supporting variables that can be used in future research are organizational support, leadership support or organizational culture.